Media Pembelajaran Kamus Bahasa Latin Berbasis Android - Al Amri; Sumitro Sarkum; Iwan Purnama (Universitas Islam Sumatera Utara, 2018)
The Latin Dictionary is a learning medium that can give ease to teachers and students at SMK AL-AZIZ. The phenomenon that occurs is the students in the class have constraints with the Latin language plants to complete the task given by teachers in fulfilling the contribution of learning that is needed in the process of learning on science subjects. This app is designed using eclipse, Waterfall Methods, UML, and SQLite databases. The design of this application is expected to be useful for students, teachers, even the general public.